(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
This paper gives a detailed analysis of the physics of simple pendulum and the equations governing the motion and velocity. The pendulum works in three modes: simple, damped and driving and driving only. The signatures are evaluated and simulated by the means of four different approaches: Euler method, Euler-Cromer method, 2nd order Runge-kutta method and built-in ODE-23 matlab solver. The simulation results are compared to the measured radar signatures using a CANTENNA RADAR originally developed by MIT. The radar was operated in Doppler mode and the micro-Doppler effects associated with pendulum is studied. This paper attempts to provide an in-depth background and analysis of how the pendulum works and the associated micro-Doppler study using RADAR.